Efficacy of Peanut Paste as Functional Component in Premium Mutton Nuggets. Issue 3 (30th June 2016) - Kumar, R.R.; Sharma, B.D.; Mendiratta, S.K.; Malav, O.P.; Talukder, S.; Irshad, A.
Abstract: Nuts besides favorable fatty acid and nutrient profile posse certain bioactive/functional compounds which elicit numerous health benefits. Premium mutton nuggets with improved nutrient profile were developed by substituting the traditionally added animal fat in emulsion by incorporation of peanut paste. With the aim to substitute added fat by 50, 75 and 100%, three levels of peanut paste viz 10, 15 and 20% were explored to determine the optimum level of their incorporation. The premium products were further analyzed and compared for detailed product profile which included lipid profile, calorific value, dietary fiber, antioxidant activity and texture profile. Based on physico‐chemical and sensory scores, the level of incorporation for peanut paste was adjudged as high as 20%. Developed premium mutton nuggets had significantly less cholesterol content, increased dietary fiber, enhanced antioxidant activity and acceptable texture profile. Thus, it was concluded that functionality components of peanut can be well incorporated to conventional processing to develop superior products. Practical Applications: The paper presents the development of novel kind of meat products enriched with Peanut paste. Incorporation of peanut paste not only substituted the animal fat improving lipid profile and antioxidant activity but also able to economize the production cost and thus stretching the availability of products among masses. Research seems to be of direct industrial application besides opening up the avenues of further research on functional components and their clinical correlation. Development of premium product using the peanuts and red meat from culled sheep stock present the most judicious way of their utilization for healthy meat products. In under developed countries and naturally dried land areas such as African countries and deserts where healthy functional meat products is beyond the reach, the recipe suggested may prove to be promising source of nutrients utilizing the native resource sheep and peanuts.